Corticosteroid Therapy Benefits Septic Mice With Adrenal Insufficiency But Harms Septic Mice Without Adrenal Insufficiency*. Issue 11 (November 2015) - Ai, Junting; Guo, Ling; Zheng, Zhong; Wang, Shu-Xia; Huang, Bing; Li, Xiang-An
Abstract : Objectives: Corticosteroid therapy is frequently used in septic patients given the rationale that there is an increased demand for corticosteroid in sepsis, and up to 60% of severe septic patients experience adrenal insufficiency. However, the efficacy of corticosteroid therapy and whether the therapy should be based on the results of adrenal function testing are highly controversial. The lack of an adrenal insufficiency animal model and our poor understanding of the pathogenesis caused by adrenal insufficiency present significant barriers to address this long-standing clinical issue. Design: Prospective experimental study. Setting: University laboratory. Subjects: Scavenger receptor BI null and adrenal-specific scavenger receptor BI null mice. Interventions: Sepsis was induced by cecal ligation and puncture. Measurements and Main Results: Using scavenger receptor BI –/– mice as the first relative adrenal insufficiency animal model, we found that corticosteroid therapy significantly improved the survival in cecal ligation and puncture–treated scavenger receptor BI –/– mice but causes more septic death in wild-type mice. We identified a corticosteroid cocktail that provides effective protection 18 hours post cecal ligation and puncture; using adrenal-specific scavenger receptor BI –/– mice as an inducible corticosteroid–deficient animal model, we found that inducible corticosteroid specifically suppresses interleukin-6 production without affecting tumor necrosis factor-α, nitric oxide, and interleukin-10 production. We further found that inducible corticosteroid does not induce peripheral lymphocyte apoptosis but promotes phagocytic activity of macrophages and neutrophils. Conclusions: This study demonstrates that corticosteroid treatment benefits mice with adrenal insufficiency but harms mice without adrenal insufficiency. This study also reveals that inducible corticosteroid has both immunosuppressive and immunopermissive properties, suppressing interleukin-6 production, promoting phagocytosis of immune effector cells, but not inducing peripheral lymphocyte apoptosis. These findings support our hypothesis that corticosteroid is an effective therapy for a subgroup of septic patients with adrenal insufficiency but harms septic patients without adrenal insufficiency and encourage further efforts to test this hypothesis in clinic. Abstract : Supplemental Digital Content is available in the text.